2007
DOI: 10.1176/ajp.2007.164.4.591
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Family Therapy and Cognitive Behavior Therapy Guided Self-Care for Adolescents With Bulimia Nervosa and Related Disorders

Abstract: Compared with family therapy, CBT guided self-care has the slight advantage of offering a more rapid reduction of bingeing, lower cost, and greater acceptability for adolescents with bulimia or eating disorder not otherwise specified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
179
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(190 citation statements)
references
References 13 publications
8
179
1
1
Order By: Relevance
“…Schmidt et al43 compared family therapy to cognitive behavioral therapy guided self-care (CBT-GSC) for 85 adolescents. The family therapy in this study was similar to FBT-BN, but differed in that adolescents were allowed to choose “close others” other than parents in their treatment, and a quarter of patients chose this option.…”
Section: Empirical Evidence For Family-based Treatment For Bnmentioning
confidence: 99%
“…Schmidt et al43 compared family therapy to cognitive behavioral therapy guided self-care (CBT-GSC) for 85 adolescents. The family therapy in this study was similar to FBT-BN, but differed in that adolescents were allowed to choose “close others” other than parents in their treatment, and a quarter of patients chose this option.…”
Section: Empirical Evidence For Family-based Treatment For Bnmentioning
confidence: 99%
“…Results from this seminal study favored the application of this approach for patients with less than a three-year duration of AN, and the body of studies to immediately follow therefore focused exclusively on adolescent AN (Eisler, Dare, Hodes, Russell, Dodge, & Le Grange, 2000; Eisler, Simic, Russell, & Dare, 2007; Le Grange, Eisler, Dare, & Russell, 1992). Since the original collection of randomized controlled trials (RCTs) of FBT was conducted, the approach has been disseminated and tested beyond the Maudsley (Le Grange, Crosby, Rathouz, & Leventhal, 2007; Lock, Agras, Bryson, & Kraemer, 2005; Lock, Couturier, & Agras, 2006; Loeb, Walsh, Lock, Le Grange, Jones, Marcus, Weaver, & Dobrow, 2007; Robin, Siegel, Moye, Gilroy, Dennis, & Sikand, 1999; Schmidt et al, 2007), and is now being adapted for a more transdiagnostic spectrum. There are currently FBT manuals for the treatment of AN (Lock, Le Grange, Agra, & Dare, 2001) and BN (Le Grange & Lock, 2007), which have both been tested in studies that included subthreshold and atypical (i.e., EDNOS) cases (Le Grange et al, 2007; Lock et al, 2005; Lock et al, 2006; Loeb et al, 2007); for the prevention of AN in symptomatic children and adolescents at high risk for developing the full disorder (Loeb, Le Grange, & Lock, 2005); and even for the treatment of adolescent overweight and obesity (Loeb, Celio Doyle, Le Grange, Bremer, Hildebrandt, & Hirsch, 2006), which can be associated with disordered eating but are not categorized as psychiatric disorders.…”
Section: Transdiagnostic Conceptualizations Of Eating Disordersmentioning
confidence: 99%
“…Individuals who engage in extreme weight loss behaviours were less likely to engage in health-promoting weight maintenance strategies such as fruit and vegetable consumption (Story, Neumark-Sztainer, Sherwood, Stang, & Murray, 1998). Several studies comparing the diagnosis of BN to subthreshold forms of this disorder found no difference in comorbid symptom severity or treatment response (Binford & le Grange, 2005; Le Grange, Crosby, Rathouz, & Leventhal, 2007; Schmidt et al, 2007). These results portend harm: Adolescents engaging in even subthreshold levels of extreme weight loss strategies are positioned on a harmful trajectory predictive of unhealthy weight management and increased eating disturbance and appear to be as ill as threshold forms of BN.…”
Section: Changes To Criteria For Inappropriate Compensatory Mechanismmentioning
confidence: 99%